Aplicação do concreto de ultra alto desempenho em viga pré-moldada protendida para pontes - Barbosa, Jadson da Silva (2021)
Several requirements and challenges of modern construction motivated the development of High-Performance Concrete (HPC) and later, with the advance of the research, the Ultra-High Performance Concrete (UHPC). Due to the seek for a concrete that was not only higher in compressive strength, but also with good tensile and ductility behavior, self-compacting, and very high durability. Composed primarily by portland cement, silica fume, quartz powder, small aggregate, steel fibers, super plasticizing additives and water, UHPC first research was developed around 1990 in France and Canada. This material can reach high strength, in the range of 150 MPa to 800 MPa for compression and 5 MPa to 100 MPa for tension, with high ductility. These characteristics allow more durable and slender structures. In addition, there is the possibility to reduce or eliminate the passive reinforcements, in particular shear. The aim of this work is to introduce criteria for structural design using UHPC, as well as its composition, production, curing methods and the main factors that hinder its use in a greater number of constructions. This text organizes all relevant information on the topic, developing a material capable of guiding engineers in the design of structures using this technology, and with that, to encourage their use in the various fields of the civil construction industry in Brazil. The research is composed by a literature review including research already developed on the subject in Brazil and in several other countries, describing the main constructions already executed with this material, design criteria, constructive details and the characteristics that differs it from conventional concretes. As application examples, prestressed bridge girder beam designs are developed using the CUAD and compared with prestressed concrete design using conventional concrete for a feasibility analysis. With the study, it was possible to clearly expose all the information necessary for its design, production and structural application, in addition to providing a material capable of guiding the design of structures using UHPC and also serving as a contribution to future technical normalization.